MlNERALOGICAL AND STABLE ISOTOPIC STUDY OF ANCIENT WHITE MARBLE QUARRIES IN LARISA, THESSALY, GREECE - Melfos, V. (Bulletin of the Geological Society of Greece, 2004)
The present work focuses on the white marbles which were extracted in Larisa prefecture, Central Greece, during the antiquity. Three characteristic ancient quarries, which are located in the Kastri village (Aghia area), in Kalochori (Sykourio area) and in Gonnoi (Tembi area), were selected for the present study. Data obtained from the extraction techniques are combined with the geological, mineralogical and stable isotopie features in order to determine these marble ancient sources. The average 513C and δ180 values of the Kastri marble are +2.80%o and 4.51 %o and of the Kalochori marble +0.87%o and -8.33%o. At Gonnoi ancient quarrying sites, the isotopie results are heterogeneous: +1.05%o ö13C, -4.65%o δ180 for Gonnoi 1 A, +1 89%o 513C, -7.97%0 δ180 for Gonnoi 1B, +2.27%o 513C, -3.12%o δ180 for Gonnoi 3.